The protection of historical wrecks in South African waters - Pugh, Lewis William Gordon (Institute of Marine and Environmental Law, 2021)
Since 1488, when Bartholemeu Dias first rounded the Cape, countless ships have been wrecked off the South African coast. Many of these ships are today of immense historical, archaeological and cultural value. Accordingly, they require protection from the threat of indiscriminate salvors. In this thesis, I shall examine to what extent current South African legislation protects and preserves historical shipwrecks which lie within twenty-four nautical miles of the South African coast. In so doing, I shall analyse the provisions of the National Monuments Act ' and draft legislation compiled in 1988 dealing with historic wrecks and artifacts '. I shall then examine to what extent the draft legislation remedies shortcomings in the National Monuments Act. However, in examining the law relating to historical shipwrecks, a familiarity with the history behind these shipwrecks is both interesting and necessary. Only then does it become evident that South Africa is steeped in shipwreck history, and that the South African coastline is a veritable treasure house.